Síndrome metabólico I : acuerdos y desacuerdos en su definición y diagnóstico (2005)
ABSTRACT: Metabolic syndrome is a complex disorder that its prevalence is increasing in all over the world. Metabolic syndrome is characterized by several metabolic abnormalities that occur together like abdominal obesity, insulin resistance, dyslipidemia and hypertension; the cluster of these abnormalities presents in patients could increase the risk of cardiovascular disease and type 2 diabetes, The main causes of death in developed and developing countries. Different international scientific associations have attempted to establish a clear definition and what diagnosis criteria is useful to define the syndrome, that has been found to be associated with cardiovascular disease and diabetes. Early detection, treatment and prevention is the main purpose for clinical practicioners. A review is presented after exhaustive scientific exploration.